Protecting privacy to protect mental health: the new ethical imperative - Aboujaoude, Elias (Journal of medical ethics, 2019)
Confidentiality is a central bioethical principle governing the provider–patient relationship. Dating back to Hippocrates, new laws have interpreted it for the age of precision medicine and electronic medical records. This is where the discussion of privacy and technology often ends in the scientific health literature when Internet-related technologies have made privacy a much more complex challenge with broad psychological and clinical implications. Beyond the recognised moral duty to protect patients’ health information, clinicians should now advocate a basic right to privacy as a means to safeguard psychological health. The article reviews empirical research into the functions of privacy, the implications for psychological development and the resigned sentiment taking hold regarding the ability to control personal data. The article concludes with a call for legislative, educational and research steps to readjust the equilibrium between the individual and ‘Big Data’.